Numerical simulation of heat recovery from asphalt pavement in Finnish climate conditions - Songok, Joel; Mäkiranta, Anne; Rapantova, Nada; Pospisil, Pavel; Martinkauppi, Birgitta (Elsevier, 2023)
A 3-dimensional mathematical model of asphalt pavement system was developed, based on the fundamental energy balance, to calculate temperatures beneath asphalt surface using hourly measured solar radiation, air temperature and wind velocity data. The modelling was conducted to predict the heat retention under the asphalt surface to seek an optimum position of pipe tubing to maximise the heat extraction considering the Nordic winter conditions for future infrastructure projects. The model results show good agreement with the experimental results conducted in a span of three months (June–Sept) notwithstanding the simplification of the model i.e. thermal properties unaffected by changing moisture content, perfect contact between different layers and homogeneous and isotropic thermal properties of materials (asphalt, sand and gravel). The findings indicated that the positioning of the heat extraction tubes under the asphalt layer will be dictated by the application. For heat extraction, pipes closer to the surface are ideal for maximal heat absorption during summer, however, in winter the outer temperature may effect properties the pipes. Parameters including pipe diameter, positioning of the pipes and flow rate were analysed. Temperature increase of up to 10 °C gain was observed for piping closer to the asphalt layer and 6 °C for pipes position at deeper from the asphalt layer. This model could be used in future to optimise critical variables for successful implementation of asphalt heating concepts.
Keywords: Heat harnessing; Asphalt surfaces; Mathematical models; Solar irradiation; heat transfer; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkötekniikka|en=Electrical Engineering|